Cream-skimming through PPAs: Interactions between private and public long-term contracts for renewable energy - Mats Kröger (Deutsches Institut für Wirtschaftsforschung (DIW), 2024)
Public support systems and private investments in renewable energy are increasingly existing side-by-side and are both emphasized in policy proposals on the European and national levels. This paper assesses the interaction between the two approaches with respect to cream-skimming, i.e., the potential for low-cost projects to sign private contracts that increase the costs of publicly supported renewable energy. This paper uses a stylized microeconomic model and a numerical simulation to assess this question. It finds that the incentive to cream-skimming exists when governments employ any form of resource differentiation in their renewable energy contracts. The numerical analysis shows that, at current price levels, cream-skimming could increase power prices by 2-6% depending on the PPA's mark-up. The effect is larger for a wider cost-distribution of renewable energy projects, which might occur as the energy transition proceeds.
Keywords: D44; Q42; Q48; 330; climate policy; renewable energy; distributional consequences; creamskimming; contracts for differences